Aplicação única de crioterapia de imersão como tratamento de gota experimental em ratos wistar - Pradal, Lilian de Araujo (2021)
Gout is an inflammatory arthritis characterized by the presence of monosodium urate crystals in peri and intra-articular space and is associated with hyperuracemia. The traditional treatment model is drug therapy, which can be costly and presents risks such as drug interaction and poor compliance, while alternative and adjunctive therapies have shown promise. However, studies relating cryotherapy as treatment of gout are still scarce. Therefore, the aim of this research was to evaluate the effect of cryotherapy as a form of treatment in a model of gout induced by urate crystals in Wistar rats. To this end, male rats were used, thinking about 250 to 300 g, randomized into four groups (n=10), control group (CONT) animals that received PBS injection and were not treated; Gout group (GOUT) that received MSUCs injection and were not treated; control treatment group (CRYO) received PBS solution injection and were treated; injury and treatment group (GOUTCRYO) that was induced to gout and treated with cryotherapy. The animals in gout group were induced by intra-articular injection of 50 µL of micro crystals of urate (MSUCs) in PBS in right knee (1.25 mg), and animals in control group were submitted to the same physical stress but with administration of 50 µL of PBS solution. The animals were submitted to 4 evaluations, being the basal evaluation (BASAL), an evaluation after 7 hours of the induction of the gout (EV1), immediately after treatment (EV2) and after 1 hour of EV2 (EV3). The treatment was performed in a single cryotherapy session, lasting 10 minutes and water temperature between 7 ºC and 10 ºC. All animals were evaluated for nociceptive threshold, joint swelling, and plantar grip strength. At the end of the experiment, the animals were euthanized by deep anesthesia and synovial fluid was collected from knee joint of right pelvic limb. Data were tabulated in Microsoft Excel® spreadsheets, and analyzed in SPSS® and GraphPad Prism® software. The experimental gout model was effective in mimicking the characteristic signs of the disease, with decreased nociception threshold, increased joint diameter, decreased grip strength, and altered synovial inflammatory pattern. The cryotherapy treatment protocol promoted increased nociception threshold (p<0.001), return and maintenance of grip strength (p<0.05), but did not reduce joint swelling (p>0.05). In leukocyte count, the experimental groups were different from the controls (p<0.001), but statistically equal to each other (p=0.142) showing higher cell concentration. The results suggest that cryotherapy is efficient in the management of nociception and return of muscle strength, and may be used as adjuvant treatment of gout, aiming to reduce the doses of drug treatment.